UJI IN VITRO DAN IN VIVO EKSTRAK HIBUSCUS SABDARIFFA SEBAGAI ANTIBAKTERI SALMONELLA TYPHIMURIUM - Iwan Doddy Dharmawibawa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
Flower H. sabdariffa is efficacious as an antiseptic, demulcent (neutralizes stomach acid), digestif (diuretic digestion, onthemintic (anti-worms), refrigerant (cooling effect), and treat cancer, cough, stomach ulcers, bloating abdomen, and prevent liver disease However, clinical trials utilizing H. sabdariffa to prevent and treat S. typhimurium infection infections have not been done. Therefore, this study was conducted to determine the effect of H. sabdariffa inhibit the growth and kill the bacteria causing S. typhimurium infection disease on The extraction of H. sabdariffa was performed by infusa method using aquadest solvent in vitro test by using the well method by measuring the diameter of clear zone formed around the well. After that, it was continued by in vivo test by giving oral extract of H. sabdariffa to the mice which has been infected S. typhimurium. From this study dipe it is found that the extract of H. sabdariffa has an antibacterial effect with the inhibitory zone obtained.